A fotografia na palma da mão: fotografia móvel nos processos de edição jornalística - Oliveira, Pedro Revillion de (Universidade do Vale do Rio dos Sinos, 2015)
The contemporary society is characterized by the great quantity of images in circulation. One of the devices responsible for this great phenomenom is the mobile phone, wich in his great majority presents a built-in photographic camera. Thousands of persons produce images intensively whith these devices and then publish in social networks millions of photographs each minute. Whith this scenery, photojournalism and the work of the professional photographer is being put in discussion. Photojournalism is recives a great amount of pressure by this contemporary making of photography. Acknowledging this environment, this study intends to understand what are the transformations that mobile photography is forcing on the processes of image editing in the ambience of a newspaper and also on the workflow of the photojournalist. To do that, the reasearch involves the observation and folowing of the pratices and produtions in photojournalism of the Zero Hora newspaper, from Porto Alegre/Brazil. In this reasearch was detected, among whith many other aspects, that there is continuous transformation of the photographic process, that goes trough adaptives stages, yet still not consolidated and with diversicated tension points.
Keywords: Fotografia; Fotojornalismo; Fotografia móvel; Edição de imagens; Photography; Photojournalism; Mobile photography; Image editing; ACCNPQ::Ciências Sociais Aplicadas::Comunicação